BEBAN DAN PSYCHOLOGICAL WELL BEING PADA KELUARGA PASIEN YANG MENJALANI HEMODIALISIS - Ashar Prima; Amzal Mortin Andas; Fauziah H Wada; Indah Puspitasari; Maratun Shoaliha; Asmiana Saputri Ilyas (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
The psychological needs of the family as caregivers are often ignored and not fulfilled by health workers, this is because caregivers are not fully planned in patient care management. This can have a negative impact on the treatment process for HD patients. There is still little information about the burden and phychological well-being of HD patients in Indonesia because some studies only focus on the burden on HD patients. Therefore this study focuses on assessing the burden and psychological well-being of caregivers of hemodialysis patients. This study aims to assess the burden and psychological well-being and its relationship with the demographic characteristics of hemodialysis patients. This study used a cross-sectional and analytic descriptive design involving 197 family caregivers of hemodialysis patients. Data collection was carried out at two hemodialysis centers in the city of Bekasi, from July to August 2022. A consecutive sampling technique was used to select research respondents. Data collection used a demographic characteristic questionnaire, Zarit Burden Interview (ZBI) and Ryff's Psychological Well-Being Scale – 18 Items (RPWB-18). Demographic characteristics data is presented in the form of frequency, mean percentage and standard deviation. Spearman rank test is used to see the correlation of variables. The results showed that the average ZBI score was 47.87 ± 12.16 and the PWB score was 70.20 ± 10.37, the correlation coefficient was -0.756, the P-value was 0.0001, indicating that there is a significant negative correlation between family burden and psychological well-being, which means that the greater the score family burden, the lower the psychological well-being score. Based on the results of this study, the needs of the family as caregivers need to be one of the focuses of providing nursing care by nurses.